Knowledge and practices related to COVID-19 among mothers of under-2 children and adult males: a cross-sectional study in Bangladesh - Talukder, Animesh; Islam, Muhammed Nazmul; Sarker, Malabika; Goswami, Indranil; Siddiqua, Rubaiya Riya; Akter, Fahmida; Chowdhury, Srizan; Chowdhury, Imran Ahmed; Rahman, Albaab-Ur; Latif, Mahbub (BMJ open, 2022)
Objectives To assess the knowledge and practices related to COVID-19 among Bangladeshi mothers with children aged 2 years or less and adult males. - Design We conducted a cross-sectional study to assess the knowledge and practices using a multistage cluster sampling technique. - Settings Six districts with high COVID-19 infection rates in Bangladesh. - Participants 2185 mothers of under-2 children and 657 adult males were surveyed in December 2020. - Main outcome measures We constructed weighted composite knowledge and practice scores and examined associations between composite scores and background characteristics using linear regression models. - Results Knowledge on possible routes of transmission of the novel coronavirus and the critical handwashing and mask-wearing etiquettes was poor. On a scale of 100, the mean composite knowledge scores of mothers and adult males were respectively 33.5 (SD=15; 95% CI 32.9 to 34.1) and 38.2 (SD=14.8; 95% CI 37.1 to 39.4). In contrast to knowledge, adult males obtained lower practice scores than mothers, primarily due to poor physical distancing practices. The mean practice scores of mothers and adult males were 63.0 (SD=18.1; 95% CI 62.3 to 63.8) and 53.4 (SD=17.5; 95% CI 52.0 to 54.7). Moreover, education, household income and access to television and the internet are significantly associated with knowledge. People residing proximal to a city revealed higher knowledge than the relatively distant ones. This was also the case for practice scores; however, the other factors associated with knowledge did not have a significant association with practices. - Conclusions In general, both mothers and adult males presented with poor knowledge and practices related to COVID-19. While local, national and international institutions should design and implement educational interventions to help improve knowledge, our research shows that mere knowledge may not be enough to ensure practice. Hence, authorities could reinforce positive social norms by setting benchmarks and introducing rewards or sanctions to improve practices.
Gesehen am 07.07.2022